The Effect of Location, Price and Product Design on Consumer Purchase Interest in Sri Jaya Meubel Bogor - Adelia Pratiwi; Titiek Tjahja Andari; Samsuri (MultiTech Publisher, 2023)
This study aims to analyze and identify the effect of location, price, and product design either simultaneously or partially on consumer buying interest at Sri Jaya Meubel Bogor. Questionnaires were distributed to 100 respondents who were taken by purposive sampling technique. The questionnaire has been tested with validity test, reliability test and classical assumption test. The test results are valid, reliable and can be used for regression data. The analytical method used in this research is descriptive and verification method with a quantitative approach. The results showed that the variables of location, price and product design either simultaneously or partially had a positive and significant effect on consumer buying interest at Sri Jaya Meubel Bogor.